Quantifying the Effects of Climate Factors on Carbon Monoxide Poisoning: A Retrospective Study in Taiwan - Wang, Chien-Ho; Shao, Shih-Chieh; Chang, Kai-Cheng; Hung, Ming-Jui; Yang, Chen-Chang; Liao, Shu-Chen (Frontiers in Public Health, 2021)
Abstract Background: Carbon monoxide (CO) poisoning is the leading cause of poisoning death worldwide, but associations between CO poisoning and weather remain unclear. Objective: To quantify the influence of climate parameters (e.g., temperature, relative humidity and wind speed) on the incidence risk of acute CO poisoning in Taiwan. Methods: We used negative binomial mixed models (NBMMs) to evaluate the influence of weather parameters on the incidence risk of acute CO poisoning. Subgroup analyses were conducted, based on the seasonality and the intentionality of acute CO poisoning cases. Results: We identified a total of 622 patients (mean age: 32.9 years old; female: 51%) with acute CO poisoning in the study hospital. CO poisoning was associated with temperature (beta: -0.0973, rate ratio (RR): 0.9073, p<0.0001) but not with relative humidity (beta: 0.1290, RR: 1.1377, p=0.0513) or wind speed (beta: -0.4195, RR: 0.6574, p=0.0806). In the subgroup analyses, temperature was associated with the incidence of intentional CO poisoning (beta: 0.1076, RR: 1.1136, p=0.0333) in spring and unintentional CO poisoning (beta: -0.1865, RR: 0.8299, p=0.0184) in winter. Conclusion: Changes in temperature affect the incidence risk for acute CO poisoning, but the impact varies with different seasons and intentionality in Taiwan. Our findings quantify the effects of climate factors and provide fundamental evidence for healthcare providers to develop preventative strategies to reduce acute CO poisoning events.